Assessing the readiness paradox of coastal ecotourism: A socio-technical evaluation of natural attraction versus infrastructure capability - Deriana Impiana; Kahirun; Safril Kasim; La Gandri; Eka Rahmatiah Tuwu (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This study aims to assess the feasibility status of the development plan for Kampa Beach, a coastal destination located in Wawobili Village, West Wawonii District, within the administrative area of Konawe Islands Regency, Indonesia. Method: The study utilized a combination of purposive sampling for stakeholders, accidental sampling for 15 visitors, and a 10% sample of the 270 local residents in Wawobili Village. The research employed the ADO-ODTWA Guidelines as the methodological framework, applying seven established assessment criteria to evaluate the site’s potential for sustainable ecotourism development. Finding: The findings reveal that the Kampa Beach Tourism Area is feasible and holds strong potential to be developed into a premier ecotourism destination. The natural tourism attraction aspect achieved a very high index score of 85.14%, followed by accessibility with 82.26%. However, the accommodation availability criterion showed a relatively low score of 33.33%, while supporting facilities and infrastructure scored 60%, placing it in a mid-range category. The security criterion recorded the highest score of 91.66%, supported by environmental conditions and local community support (90%) and linkages to nearby tourist attractions (77.5%). While five criteria meet the requirements for full development, the lack of lodging and basic amenities requires immediate intervention. Conclusion: The composite calculation of all indicators yields a final average score of 74.27%, confirming Kampa Beach’s feasibility as a potential ecotourism area. The results also highlight key areas requiring priority interventions to ensure optimal and sustainable development. Novelty/Originality of this article: This study identifies a unique readiness paradox in Wawobili Village, where the natural attractiveness and community safety indices have reached elite levels (above 90%), but are hampered by severe delays in accommodation infrastructure (33%). Unlike general tourism reviews, this study identifies specific socio-technical barriers that must be overcome to transform this remote coastal site into a sustainable premier destination.